Collagen hydrolysate intake improves the loss of epidermal barrier function and skin elasticity induced by UVB irradiation in hairless mice. Issue 4 (1st July 2013) - Oba, Chisato; Ohara, Hiroki; Morifuji, Masashi; Ito, Kyoko; Ichikawa, Satomi; Kawahata, Keiko; Koga, Jinichiro
Summary Background Ultraviolet B (UVB) irradiation induces serious damage to the skin. Collagen hydrolysate and collagen‐derived peptides have effects on skin function in vivo and in vitro. However, few studies have investigated changes in the epidermal barrier or dermal elasticity caused by UVB. Here, we investigated the loss of epidermal barrier function and skin elasticity induced by UVB irradiation in hairless mice fed collagen hydrolysate. Methods Mice were orally administered collagen hydrolysate, in a single dose (20 mJ/cm2) or repeated doses (10–30 mJ/cm2, 3 times/week for 6 weeks), and the dorsal skin was exposed to UVB. Skin measurements and histological and analytical studies were performed. Results In control mice, a single UVB irradiation induced epidermal barrier dysfunction including an increase in transepidermal water loss (TEWL), epidermal hyperplasia, and a decrease in stratum corneum water content. Administration of collagen hydrolysate significantly decreased TEWL and epidermal thickness and increased stratum corneum water content. Repeated UVB irradiation decreased skin elasticity and dermal hyaluronic acid (HA) content in control mice, whereas collagen hydrolysate significantly suppressed both the increase in TEWL and the decrease in stratum corneum water content and improved skin elasticity and dermal HA content. Conclusions Collagen hydrolysate administration affects epidermal barrier function and dermal skin elasticity.